Pengaruh Model Pembelajaran SAVI (Somatis, Auditori, Visual, dan Intelektual) Terhadap Peningkatan Self-Efficacy Matematika Siswa di Sekolah Menengah Atas - Fatmawati, Alfi; Nuryadi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aimed to enhance the mathematical efficacy of secondary school students through the implementation of the SAVI (Somatic, Auditory, Visual, and Intellectual) learning model. The study used a quasi-experimental approach with a non-equivalent control group design, involving final-year students at SMA Negeri 1 Sedayu. The sample was determined using cluster random sampling and divided into one experimental group and one control group. Data on self-efficacy was collected using a validated questionnaire and analysed using a t-test. The results of the study showed that the SAVI learning model significantly increased self-efficacy in students compared to conventional learning (p = 0.020 < 0.05). The N-Gain value of 0.37 indicates an improvement in the moderate category for the experimental group. These findings suggest that SAVI learning, which integrates various learning modalities, is effective in building students' self-efficacy through active and collaborative learning experiences.